Variación de la distribución geográfica potencial del invasor lithobates catesbeianus (ranidae) en Ecuador continental ante escenarios de cambio climático - Mendoza Loor , Anthony Michael (2023)
The wide variety of climates present in Ecuador, as well as the diversity of its fauna, favor the expansion of invasive exotic species such as Lithobates catesbeianus. This study evaluated the variation in the potential geographic distribution of L. catesbeianus in continental Ecuador under the SSP245 and SSP585 climate change scenarios for different time periods. Presence records were collected from the Global Biodiversity Information Facility database and scientific literature. Using the kuenm package, it was revealed that the most relevant variables for the analysis are temperature and precipitation, specifically Bio1 (mean annual temperature), Bio7 (coldest annual temperature), Bio10 (mean warm quarter temperature), Bio11 (mean cold quarter temperature), and Bio11 (mean cold quarter temperature). The distribution of the species in Ecuador, Colombia, Mexico, United States and Canada was modeled and trimmed for mainland Ecuador from a total of 1581 candidate models. The species is prevalent in coastal regions, specifically in the province Guayaquil, Los Ríos, Manabí, Santa Elena and Esmeraldas. In the eastern part of Ecuador, the province Napo, Morona Santiago and Zamora Chinchipe were the most suitable for its habitat, with Zamora Chinchipe being one of the most suitable at a medium level. Presence in the Sierra is limited, but is maintained in areas close to the other regions. The analysis of climate scenarios reveals that the distribution of the species may increase in the future, especially in the coastal regions of the country. It is recommended that control and monitoring measures be implemented to prevent the expansion of the species and minimize its negative impacts on the environment and local fauna. Keywords: bullfrog, ecological niche modeling, global warming, invasive alien species, Kuenm.